Electromagnetic field-induced converse cell growth during a long-term observation. (December 2013) - Bae, Ji-Eun; Do, Ji-Yeon; Kwon, Soon-Hwan; Lee, Sang-Dae; Jung, Yong Woo; Kim, Soo-Chan; Chae, Kwon-Seok
Abstract Purpose: Professional and public concern about the potential adverse effects of man-made electromagnetic fields (EMF) on the human body has dramatically expanded in recent years. Despite numerous attempts to investigate this issue, the long-standing challenge of reproducibility surrounding alternating EMF effects on human health remains unresolved. Our chief aim was to investigate a plausible mechanism for this phenomenon. Materials and methods: Growth of cultured human cancer cells, DU145 and Jurkat, exposed to power frequency magnetic field (MF) (60 Hz, 1 mT) for 3 days, was determined using a 2-(4-Iodophenyl)- 3-(4-nitrophenyl)-5-(2, 4-disulfophenyl)-2H-tetrazolium (WST-1) assay and a trypan blue exclusion assay. This experiment was repeated at incubators long-term monitoring period up to 5.3 years. A periodogram analysis was performed to investigate periodic patterns in the MF and sham effects on cell growth. Results: Unlike conventional assumptions, the MF effect on growth in both cell types was promotive or suppressive in a period-dependent manner. The converse cell growth induced by the MF was consistent in incubators, with little variation. Conclusions: Spatiotemporal evidence suggests that the period-dependent converse cell growth by the MF may contribute to the poor reproducibility and explain the adverse effects observed in previous experimental and epidemiological investigations. Additionally, the novel approach of this study may be applied to design features required to experimentally determine the effects of EMF on living organisms in a convincing manner.